(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The planet is divided between people who are alive and those who are deceased. However, a sizable portion belongs to people who have not yet been born. Anticipatory and participative development techniques are necessary for informed decision-making on the best use of natural resources and sustainable development to ensure that development and environmental health go hand in hand. One of these tools is the environmental impact assessment (EIA). This essay aims to define the idea of environmental impact assessment (EIA) and analyse its numerous components, including its basic ideals, guiding principles, shortcomings, and recommendations for improvement.